REVERSE ENGINEERING TERHADAP ANALISIS TEGANGAN BACK LADDER PESAWAT DHC-6 TWIN OTTER 300S DENGAN METODE ELEMEN HINGGA - SETYO DEWANTORO (2021)
Basically, a structure can accept a force and type of loading that varies with tolerable wear limits, because the force received can cause a structure to experience deformation to the failure of the structure. Likewise with the aircraft structure, it must be made strong in order to be able to withstand the forces to be received. Because every component in an airplane is an important part. The aircraft component that will be discussed inothisothesisois the back ladder on the DHC-6 Twin Otter 300S aircraft. By applying the reverse engineering method to the design of the back ladder structure, using aluminum as a material variation, and simulating the fluent and structural strength using FEA software. Then it produces a modified version of the back ladder that is more aerodynamic and ladderstep, a variation of the alluminum 7075 material that is more proper for access to and from passengers.